Thermal death kinetics of adult red flour beetle Tribolium castaneum (Herbst) in canola seeds during radio frequency heating. Issue 12 (2nd December 2017) - Yu, Daeung; Shrestha, Bijay; Baik, Oon-Doo
ABSTRACT: Thermal mortalities of adult red flour beetles Tribolium castaneum (Herbst) infesting canola seeds at various moisture contents and volumes were determined after radio frequency (RF) heating (i.e. temperature between 30 and 80°C). The mortality of 92% was achieved at the end temperature of 343 K for small-volume (1.96 × 10 −4 m 3, 0.250 kg) seeds, and the mortality of 99% at 333 K for large-volume (1.77 × 10 −3 m 3, 2.26 kg) seeds. Regardless of sample volume, the thermal mortalities of the test insects increased significantly after the seed temperature reached 333 K (60°C). The kinetic parameters of the thermal death of the adult T. castaneum were estimated using inverse simulation. The ordinary differential equation-based kinetic model with the Arrhenius temperature-dependent reaction rate constant was solved using the fourth-order Runge–Kutta method. The kinetics followed first-order reaction with the activation energy of 100 kJ/mol. Good agreements were observed between the mortalities predicted using the kinetic model and the experiments ( R 2 = 0.972–0.987) except for the small-volume seeds at 11% MC (11 g/100 g raw materials) ( R 2 = 0.741). The predicted lethal times (s) to achieve 95 and 99% mortalities using the kinetic model agreed well with those determined from the experiments.